Language and Gender in Pashto: A Study of Linguistic Sexism in Everyday Discourse - Saqib Raza,; Dr. Syed Azaz Ali Shah,; Dr. Said Imran, (Al-Qanṭara, 2024)
Sexist language refers to any language that is intended to be inclusive of all genders but inadvertently (or otherwise) excludes one gender, whether male or female. Examining linguistic sexism involves exploring the connection between language and gender. The Pashto language, reveals significant gender biases deeply embedded in its semantics, morphology, syntax, and proverbs This research explores these biases through a comprehensive analysis of semantics, morphology, syntax, and proverbs. Semantic analysis reveals that words associated with men typically convey strength and authority, while those linked to women often carry negative or diminished connotations, reflecting broader societal undervaluation of women. Morphological examination uncovers how gender-specific suffixes in Pashto diminish the status of women, reinforcing traditional power dynamics. The syntactical analysis highlights the default male interpretation and the imposition of gender-specific roles through sentence structures and pronoun usage, further entrenching male dominance and female subordination. Finally, the study of proverbs demonstrates how cultural expressions encode and perpetuate sexist attitudes, depicting women in subordinate roles and reinforcing their confinement to the domestic sphere. Collectively, these linguistic sexist elements not only mirror but also contribute to the maintenance of a patriarchal social order in Pashtun society. Addressing these biases is crucial for challenging and dismantling the deep-rooted gender inequalities that persist within this cultural context.